2018
DOI: 10.1002/jcp.27821
|View full text |Cite
|
Sign up to set email alerts
|

OVO homologue‐like 1 promotes osteoblast differentiation through BMP2 expression

Abstract: OVO homologue‐like 1 (OVOL1) encodes a C2H2 zinc finger protein and is an evolutionarily conserved gene in mammals. The OVOL1 expression is required for development. However, the function of OVOL1 in bone metabolism remains unreported. Here, we show for the first time the role of OVOL1 in osteoblast differentiation. To determine the role of OVOL1 in osteogenic differentiation, we analyzed OVOL1 expression in the preosteoblastic cell line. OVOL1 messenger RNA expression was induced during osteoblast differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…BMP2 acts as a positive regulator of osteoblastic differentiation and promotes osteoblastic differentiation by activating the Smads signaling cascade [ 28 , 29 ]. RUNX2 expression is induced by BMP2 during osteogenic differentiation, and it can regulate the expression of osteogenic markers, such as osteocalcin (OCN), COL1A1, and osteopontin (OPN) [ 30 , 31 ]. Moreover, the high expression of BMP2 mitigates glucocorticoid-induced osteoporosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMP2 acts as a positive regulator of osteoblastic differentiation and promotes osteoblastic differentiation by activating the Smads signaling cascade [ 28 , 29 ]. RUNX2 expression is induced by BMP2 during osteogenic differentiation, and it can regulate the expression of osteogenic markers, such as osteocalcin (OCN), COL1A1, and osteopontin (OPN) [ 30 , 31 ]. Moreover, the high expression of BMP2 mitigates glucocorticoid-induced osteoporosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research showed that the binding of FN and integrin α5 could induce the intramembrane osteogenesis. The upregulation of bone morphogenetic protein 2 (BMP2), a potent osteogenic inducer, and the upregulation of matrix Gla protein (MGP), a calcification inhibitor, are considered as the key of osteoblast differentiation [22][23][24][25]. Moreover, researchers found Runx2 is also necessary for the formation of bone tissue, and it is considered to be the most important transcription factor for osteoblast differentiation and the key to osteoblast differentiation [26].…”
Section: Introductionmentioning
confidence: 99%